Assessing the empirical challenges of evaluating the benefits and risks of irrigating with wastewater - Weldesilassie, A.B.; Amerasinghe, Priyanie H.; Danso, George K. (Informa UK Limited, 2011)
In this article the authors assess the empirical challenges of estimating the costs and benefits of using wastewater in agriculture. The wide variation in the characteristics of wastewater irrigation complicates efforts to estimate costs and benefits, and to transfer such estimates across locations. They examine wastewater use in four countries in Africa and Asia, where research has been conducted for many years. They find a significant patchwork of results, but no satisfying overall assessment. The authors suggest focusing on the cost-effectiveness of interventions for risk reduction, rather than economic analyses of the full range of costs and benefits of using wastewater in agriculture.